Aquaporin 4-Mediated Glutamate-Induced Astrocyte Swelling Is Partially Mediated through Metabotropic Glutamate Receptor 5 Activation - Shi, Zhongfang; Zhang, Wei; Lu, Yang; Lu, Yi; Xu, Lixin; Fang, Qing; Wu, Min; Jia, Mei; Wang, Yujiao; Dong, Liping; Yan, Xu; Yang, Shaohua; et al. (Frontiers in Cellular Neuroscience, 2017)
Astrocytes are one of the most abundant cell types in the mammalian central nervous system, and astrocyte swelling is the primary event associated with brain edema. Glutamate, the principal excitatory amino acid neurotransmitter in the central nervous system, is released at high levels after brain injury including cerebral ischemia. This leads to astrocyte swelling, which we previously demonstrated is related to metabotropic glutamate receptor (mGluR) activation. Aquaporin 4 (AQP4), the predominant water channel in the brain, is expressed in astrocyte endfeet and plays an important role in brain edema following ischemia. Studies recently showed that mGluR5 is also expressed on astrocytes. Therefore, it is worth investigating whether AQP4 mediates the glutamate-induced swelling of astrocytes via mGluR5. In the present study, we found that 1 mM glutamate induced cell swelling, quantified by the cell perimeter, but it had no effect on rat astrocyte viability measured by the cell counting kit-8 and lactate dehydrogenase assays. Quantitative reverse transcription polymerase chain reaction analyses revealed that AQP4, among AQP1, 4, 5, 9, and 11, was the main molecular expressed in cultured astrocytes. Glutamate-induced cell swelling was accompanied by a concentration-dependent change in AQP4 expression. Furthermore, RNAi technology revealed that AQP4 gene silencing inhibited glutamate-induced astrocyte swelling. Moreover, we found that mGluR5 expression was greatest among the other mGluRs in cultured astrocytes and was co-expressed with AQP4. Activation of mGluR5 in cultured astrocytes using (S)-3,5-dihydroxyphenylglycine (DHPG), an mGluR5 agonist, mimicked the effect of glutamate. This effect was abolished by co-incubation with the mGluR5 antagonist fenobam but was not influenced by DL-threo-β-benzyloxyaspartic acid (DL-TBOA), a glutamate transporter inhibitor. Finally, experiments in a rat model of transient middle cerebral artery occlusion revealed that co-expression of mGluR5 and AQP4 was increased in astrocyte endfeet around capillaries in the penumbra, and this was accompanied by brain edema. Collectively, these results suggest that glutamate induces cell swelling and alters AQP4 expression in astrocytes via mGluR5 activation, which may provide a novel approach for the treatment of edema following brain injury.